Design synthesis and antibacterial activity studies of new thiadiazoloquinolone compounds. (December 2014) - Al-Qawasmeh, Raed A.; Abadleh, Mohammed M.; Zahra, Jalal A.; El-Abadelah, Mustafa M.; Albashiti, Rabab; Zani, Franca; Incerti, Matteo; Vicini, Paola
Abstract New 9-(alkyl/aryl)-4-fluoro-6-oxo[1, 2, 5]thiadiazolo[3, 4-h]quinoline-5-carboxylic acids and their esters were designed and synthesized. A detailed discussion of the reactions utilized in the preparation of the intermediate and target compounds is reported. All the newly synthesized compounds were fully characterized using all the physico-chemical means needed. All the intermediates and the final esters and acids were tested against bacterial and fungal strains. The acids 25a and 25c proved to be very active against Gram positive and Gram negative bacteria with MIC 0.15–3 µg/mL. The structure–activity relationship of antibacterial thiadiazoloquinolones shows that compounds 25a and 25c are twice less potent than the corresponding cyclopropyl derivative 16. Therefore, the cyclopropyl moiety on N-9 seems to be the most suitable substituent.